Technical Islamic vocabulary in Malaysian touristic masjid da'wah pamphlets - Jaramillo, Derrick Fernando (Kulliyyah of Languages and Management, International Islamic Universiti Malaysia, 2017)
This study aimed to identify the technical terms present in Malaysian touristic masjid da'wah pamphlets and gauge whether their occurrence has any significant impact on the difficulty level of the content. A total of 25 English language Islamic da'wah pamphlets were analysed in order to reach the conclusions found by the study. Two instruments were employed to collect and analyse the data; the first instrument was a four level scale to classify lexical items and the second instrument was a readability formula developed by textbook publisher Robert Gunning. The findings of the study show that a considerable amount of technical vocabulary is employed in the pamphlets. Consequently, most pamphlets analyzed were found to possess a low readability level due to their scores being above the easy-reading line. As past studies have demonstrated, the vocabulary of a text plays a major part in the understanding of it, thus, this research would assert that the lexical items employed in these da'wah pamphlets may hinder readers from appropriately grasping the Islamic concepts elaborated within them.